Anemia following Roux-en-Y gastric bypass for morbid obesity; a 5-year follow-up study. (3rd August 2018) - Engebretsen, K. V.; Blom-Høgestøl, I. K.; Hewitt, S.; Risstad, H.; Moum, B.; Kristinsson, J. A.; Mala, T.
Abstract: Objectives: Patients are at risk of anemia post Roux-en-Y gastric bypass (RYGB). We sought to determine the prevalence of anemia and related nutritional deficiencies 5 years after RYGB and to evaluate adherence to nutritional supplements with iron, vitamin B12, and folate. Material and methods: Patients operated with RYGB 2004–2006 were eligible for evaluation. Blood samples were collected and use of nutritional supplements was recorded preoperatively, and at outpatients' consultations 1, 2, and 5 years postoperatively. Of 203 patients operated, 184 (91%) completed the 5 year follow-up and were included in the study. Of these, 97% had valid measurements of hemoglobin both at baseline and after 5 years. Results: During the 5 years after RYGB, the prevalence of anemia increased from 4% preoperatively to 24% in females, and from 0% to 7% in males. Ferritin levels decreased gradually in both genders. Iron deficiency increased from 6% preoperatively to 42% at 5 years in females, and from 0% to 9% in males. Vitamin B12 deficiency was not altered while folate deficiency decreased from 10% preoperatively to 1% at 5 years. Five years after surgery 25% reported the use of supplements with iron, while 83% used vitamin B12 and 65% used multivitamins with folate. Conclusions: We observed a long-term increase in anemia and iron deficiency after RYGB in both genders, but most pronounced in women. Our postoperative protocol for prevention of vitamin B12 and folate deficiencies appear acceptable. Iron status and iron supplementation seems to need stronger emphasis during follow-up after RYGB.